Pressure mapping to assess seated pressure distributions and the potential risk for skin ulceration in a population of sledge hockey players and control subjects - Berthold, J.; Dicianno, B. E.; Cooper, R. A. (Disability and Rehabilitation: Assistive Technology, 2013)
Purpose: Ice sledge (or sled) hockey is a fast-paced sport that enables individuals with physical disabilities to play ice hockey. As the attraction to the sport continues to rise, the need for developing better equipment and installing preventative measures for injury will become increasingly important. One such injury includes skin pressure ulceration.